Pengaruh Bimbingan Manasik Haji Terhadap Kemandirian Jamaah KBIHU Al Muhajirin Palembang - Muhammad Joko Susilo; Ahmad Syarifudin; Hidayat HT (Social Science and Contemporary Issues Journal, 2023)
This study aimed to determine the effect of guidance on Hajj rituals on the independence of pilgrims at KBIHU Al Muhajirin Palembang. The type of research used is field research and a quantitative approach using survey techniques. This study uses primary and secondary data types, primary data obtained directly from the responses of the pilgrims from KBIHU Al Muhajirin Palembang and secondary data obtained from various books, journals, and articles related to this research. This study used data collection methods by distributing questionnaires, observations, interviews, and documentation. The analysis technique used in this study is a quantitative analysis technique with a validity test, reliability test, basic assumption test (normality test, linearity test, homogeneity test), and simple linear regression analysis and hypothesis testing (t-test and coefficient of determination test). The results of the data processing using the SPSS program version 25.0 obtained a value of t-count > t-table (3.805 > 2.01063) and a significance value of 0.000 <0.05. There is an influence between variables. The results of the Coefficient value also evidence this. The determination (Adj R2) is 0.216, which shows that the effect of the Hajj Manasik Guidance variable on the Independence of the Pilgrims is 21.6%. In comparison, the remaining 78.4% is influenced by other variables that have not been studied or included in this study's regression.